2017
DOI: 10.1159/000455140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in utero and Postnatal Exposure to Secondhand Smoke on Lung Function by Gender and Asthma Status: The Seven Northeastern Cities (SNEC) Study

Abstract: Background: Little information exists on whether gender or asthma status modifies the effects of secondhand smoke (SHS) exposure on lung function. Objective: To evaluate whether gender or asthma status modifies the association of SHS exposure with lung function. Methods: A total of 6,740 children (average 11.6 years) were recruited from 24 districts of 7 cities in northeast China in 2012. SHS exposure included exposure to environmental and maternal smoking both in utero and during early childhood (postnatal). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…The Seven Northeastern Cities (SNEC) study is a large population‐based cross‐sectional study, the details of which have been previously reported . Briefly, we selected seven cities in Liaoning Province of Northeastern China (Shenyang, Dalian, Anshan, Fushun, Benxi, Liaoyang, and Dandong) from April 2012 to June 2013.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Seven Northeastern Cities (SNEC) study is a large population‐based cross‐sectional study, the details of which have been previously reported . Briefly, we selected seven cities in Liaoning Province of Northeastern China (Shenyang, Dalian, Anshan, Fushun, Benxi, Liaoyang, and Dandong) from April 2012 to June 2013.…”
Section: Methodsmentioning
confidence: 99%
“…Two study technicians measured lung function in children using electronic spirometers (Spirolab, MIR, Italy) as previously described in detail . Briefly, after 5 minutes of rest, spirometry was measured three times according to the American Thoracic Society (ATS) and European Respiratory Society (ERS) protocols, which are adjusted for body temperature and saturated pressure.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations